Determinants of Core Drives of Best Banking Award in 2018; A Case of Meezan Bank limited - Dr. Qaisar Bilal; Mr. Zulqarnain Haider (Acta-Islamica, 2021)
PURPOSE The financial institutions continue to adopt different models and techniques, with intentions to get competitive advantages and to make frequent, smooth and easy financial transactions in order to meet their predefined objectives efficiently and effectively. This race brings the institutions to the point where the strategist utilizes distinct, innovative, and ground-breaking measures to be the top player of the market. The journey of Meezan Bank limited is very inspirational and growing graph of this institute among the listed financial companies proves its stability, performance-based banking and clicking the peaks of customer satisfaction along with maintain the transactions in full conformity with Shariah Standards. It is also observed that tendency of public towards Meezan Bank is due to realistic policies touching the basis of socio-economic rehabilitation of the society in general and shooting up direct economic activities specifically. The paper emphasis on defining those determinants which has played prominent role in bringing this financial institute to top and placing it as number one player of the market among not only ranking with Islamic Banks but compete with conventional banks of Pakistan. DESIGN/METHODOLGY/APPROACH The paper deals in considering distinct aspects to get the core drives of this consistent financial journey of Meezan Bank. It covers the analysis of financial records, internal and external policies affecting the competitors, performance parameters through different statistic tools in order to get the concrete and solid measures towards success of the bank. It also constitutes the stances of sharia advisors of different Islamic banks coupled with knowing the extent of compliance with Sharia Rulings. FINDINGS The paper's findings reveal that not a single parameter is enough to give any institution competitive advantage but the key is to maintain proper rational financial model, clear and real predefined goals and objectives along with competent team is the utmost requirement to be the number one player of the market. RESEARCH LIMITATIONS The study covers the specific aspect of the Bank to give the result about its success and being leading institute not only in Pakistan but also considers one of the vibrant and efficient organization across the globe. However, there is possibility that Bank’s performance, productivity, management and strategies reflects the high growth and have competitive advantages in the market and deals extraordinary profitability is because of different hidden drives but here it has been focused on any one or two with complete details ORIGINALITY/VALUE The paper intends to bring the insights of Meezan Bank that how this institute now clicking the peaks of the financial positions along with right striving towards maintaining and sustaining the same status in coming future. This will be the real picture for other organization to follow it with true spirit for supporting the national interest in all respect along with self-profitability coupled with portraying the sketch of all determinants play prominent role in this regard so it may help the concerned to get the guidance accordingly.